2015
DOI: 10.1021/acsami.5b05466
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Assembly of Fibronectin Nanofibrils Triggered by Random Copolymer Chemistry

Abstract: Fibronectin fibrillogenesis is the physiological process by which cells elaborate a fibrous FN matrix. Poly(ethyl acrylate), PEA, has been described to induce a similar process upon simple adsorption of fibronectin (FN) from a protein solution -in the absence of cells -leading to the so-called material-driven fibronectin fibrillogenesis. Poly(methyl acrylate), PMA, is a polymer with very similar chemistry to PEA, on which FN is adsorbed keeping the globular conformation of the protein in solution. We have used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 58 publications
(121 reference statements)
1
25
0
Order By: Relevance
“…In addition, the phenomenon is rapid and allows FN organization within a time scale of ~1 min ( 28 ). Further, we have recently shown that the combination of EA and MA in a random copolymer modulates the interconnection of FN nanonetworks in dependence of the composition of the system ( 29 ). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the phenomenon is rapid and allows FN organization within a time scale of ~1 min ( 28 ). Further, we have recently shown that the combination of EA and MA in a random copolymer modulates the interconnection of FN nanonetworks in dependence of the composition of the system ( 29 ). …”
Section: Resultsmentioning
confidence: 99%
“…These results suggest a close dependence between the mobility of polymer chains and the FN organization on the surface [23], [27]. When the amount of crosslinker increases, T g rises monotonically, reducing surface mobility.…”
Section: Resultsmentioning
confidence: 60%
“…The main contribution of this work is that it shows that PEA-based 3D scaffolds sustain the organization of the fibronectin in their pores into physiological-like (nano)networks in the same way as in 2D substrates and fibres, the so-called 2.5D environments [13], [23], [24], [25], [26], [27], [33].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations